A Photochemoenzymatic Hunsdiecker‐Borodin‐Type Halodecarboxylation of Ferulic Acid. (23rd August 2022) - Zippilli, Claudio; Bartolome, Miguel Jimenez; Hilberath, Thomas; Botta, Lorenzo; Hollmann, Frank; Saladino, Raffaele
Abstract: A photochemoenzymatic halodecarboxylation of ferulic acid was achieved using vanadate‐dependent chloroperoxidase as (bio)catalyst and oxygen and organic solvent as sole stoichiometric reagents in a biphasic system. Performance and selectivity were improved through a phase transfer catalyst, reaching a turnover number of 660.000 for the enzyme. Abstract : Halodecarboxylation of α, β‐unsaturated ferulic acid was achieved by combining photo‐, bio‐ and phase transfer catalysis in a biphasic system. Reactive hypobromite was formed in situ by combining Blue‐LED and vanadium chloroperoxidase, and efficiently transferred from the aqueous to the organic layer by a phase‐transfer catalyst, improving overall performance and selectivity.